A typology of food consumption patterns in ASEAN: A cluster analysis of convergence and divergence (2010-2022) - Dama Laksita Apta Sukaton; Bartłomiej Bajan (Jurnal Inovasi Pangan dan Gizi, 2026)
Background: The Association of Southeast Asian Nations (ASEAN) is a global epicenter of the nutrition transition, where rapid economic growth, urbanization, and globalization are profoundly reshaping food consumption patterns. This study aims to quantitatively map the evolving typology of dietary patterns across ASEAN and determine whether homogenization, divergence, or a multi-polar clustering best characterizes the region's food consumption evolution from 2010 to 2022. Methods: Employing a rigorous quantitative framework, this research analyzes detailed FAO Food Balance Sheet data for eight ASEAN countries. This study calculated structural similarity indices using the Manhattan distance and performed hierarchical cluster analysis via the vector elimination algorithm to group countries based on their calorie-source composition. Findings: This study analysis reveals a clear trend of dietary multi-polarity, challenging the convergence thesis. The number of distinct dietary clusters increased from four in 2010 to five in 2022. The identified clusters include an animal protein and sugar-rich group (Philippines, Thailand, Viet Nam), a starchy staple-dependent group (Cambodia, Lao PDR), a unique palm oil and poultry-driven cluster (Indonesia), and two distinct standalone clusters (Malaysia and Myanmar). This fragmentation underscores that globalizing forces interact with local agricultural systems, cultural preferences, and path dependencies to produce sustained dietary diversity. Conclusion: This study conclude that ASEAN is experiencing a "multi-polar nutrition transition." The principal implication is that uniform, one-size-fits-all food system policies are inadequate. Instead, the identified typology provides a critical evidence base for designing targeted, cluster-sensitive interventions. Novelty/Originality of this article: This research provides the first longitudinal, cluster-based typology of ASEAN food consumption patterns over a critical period of regional integration. It challenges linear convergence theories by empirically demonstrating sustained multi-polarity and offers a novel, practical framework for cluster-sensitive policymaking.